2015
DOI: 10.1017/s1466252315000018
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification for diagnosis of 18 World Organization for Animal Health (OIE) notifiable viral diseases of ruminants, swine and poultry

Abstract: Loop-mediated isothermal amplification (LAMP) is a simple, powerful state-of-the-art gene amplification technique used for the rapid diagnosis and early detection of microbial diseases. Many LAMP assays have been developed and validated for important epizootic diseases of livestock. We review the LAMP assays that have been developed for the detection of 18 viruses deemed notifiable of ruminants, swine and poultry by the World Organization for Animal Health (OIE). LAMP provides a fast (the assay often takes les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 84 publications
1
34
0
Order By: Relevance
“…Advances in field of diagnosis for the development of sensitive and specific point-of-care diagnostic assays like LAMP, lateral flow assay, recombinant protein based diagnostics, biosensors, biochips, microarrays, genomic fingerprinting and nanodiagnostics need to be explored to their full potential for diagnosing DEV (Belak et al 2009;Ji et al 2009;Balamurugan et al 2010;Ayyar & Arora, 2013;Num & Useh, 2013;Mansour et al 2015). These assays can aid in swift diagnosis of the disease thereby preventing the spread of virus and alleviating economical loss to the farmer.…”
Section: Molecular Diagnosis Of Devmentioning
confidence: 99%
“…Advances in field of diagnosis for the development of sensitive and specific point-of-care diagnostic assays like LAMP, lateral flow assay, recombinant protein based diagnostics, biosensors, biochips, microarrays, genomic fingerprinting and nanodiagnostics need to be explored to their full potential for diagnosing DEV (Belak et al 2009;Ji et al 2009;Balamurugan et al 2010;Ayyar & Arora, 2013;Num & Useh, 2013;Mansour et al 2015). These assays can aid in swift diagnosis of the disease thereby preventing the spread of virus and alleviating economical loss to the farmer.…”
Section: Molecular Diagnosis Of Devmentioning
confidence: 99%
“…The main isothermal methods include loop-mediated isothermal amplification (LAMP; Notomi et al, 2000 ), nucleic acid sequence-based amplification (NASBA; Mugasa et al, 2014 ), rolling circle amplification (RCA; Ali et al, 2014 ), helicase-dependent amplification (HDA; Barbieri et al, 2014 ), strand displacement amplification (SDA; Qiu et al, 2013 ), isothermal and chimeric primer-initiated amplification of nucleic acids (ICANs; Asiello and Baeumner, 2011 ), and signal-mediated amplification of RNA technology (SMART; Zanoli and Spoto, 2012 ). Among them, LAMP has been widely adopted and further developed for widespread clinical use (Lee et al, 2015 ; Nakano et al, 2015 ; Neeraja et al, 2015 ; Oriero et al, 2015 ), the diagnosis of infectious diseases (Mori and Notomi, 2009 ; Kinoshita et al, 2015 ; Mansour et al, 2015 ), rapid testing of food products (D'Agostino et al, 2015 ; Ferrara et al, 2015 ; Sun et al, 2015 ) and environmental samples (Niessen, 2015 ; Shi et al, 2015 ), and also for detecting exogenous genes in GMOs (Zhou et al, 2014 ; Liu et al, 2015 ; Feng et al, 2015 ; Huang et al, 2015 ; Singh et al, 2015 ; Wang et al, 2015 ; Zhang et al, 2016 ) in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Many LAMP assays have been developed and validated for important epizootic diseases, including 18 viruses thought notifiable of ruminants, swine and poultry by the World Organization for Animal Health (OIE) (Mansour et al, 2015). The LAMP assay was also developed for detection of the Tembusu virus (Tang et al, 2016), four immunosuppressive viruses (Song et al, 2018), avian leucosis virus (Peng et al, 2015), avian reovirus (Kumar et al, 2017), and found to be useful also in the detection of MDV in feathers and internal organs of infected chickens (Woźniakowski and Samorek-Salamonowicz, 2014).…”
Section: The Loop-mediated Isothermal Amplificationmentioning
confidence: 99%